2020
DOI: 10.1088/1402-4896/abc6d9
|View full text |Cite
|
Sign up to set email alerts
|

A new generalized θ-conformable calculus and its applications in mathematical physics

Abstract: In this work, a new generalized concept of conformable derivative is given and named generalized θ–conformable derivative (GTCD). Several properties are studied such as the chain rule, the quotient rule, the product rule, the Rolle’s theorem, the mean value theorem and the fundamental theorems of calculus. Also, the geometrical and physical interpretations of the GTCD are presented. It is very easy to see that the GTCD is comprehensive and includes many past derivatives as special cases. An application of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Furthermore, in [1] the researchers showed that the conformable approach in [15] cannot yield good results when compared to the Caputo definition via specific mappings. This imperfection in the conformable description is avoided by some refinements of the conformable approach [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in [1] the researchers showed that the conformable approach in [15] cannot yield good results when compared to the Caputo definition via specific mappings. This imperfection in the conformable description is avoided by some refinements of the conformable approach [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it turns out that the LCD generalizes the traditional Newton-Leibniz derivative on a nonzero domain, but it has no correlation at zero. So, it is subjected to some criticism [1,26]. This blemish in the LCD was evaded by a new local generalized conformable derivative (LGCD), proposed by Zhao and Luo [55].…”
Section: Introductionmentioning
confidence: 99%
“…This blemish in the LCD was evaded by a new local generalized conformable derivative (LGCD), proposed by Zhao and Luo [55]. Therefore the locality and inclusiveness advantages of the LGCD give it the entitlement to occupy the place of the LCD [26,56]. Moreover, the LGCD provides a new application environment to gain some general results for many physical evolution models [25,27,55,56].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, applications of generalized calculus are frequently appeared to unveil the behavior of multiple nonlinear phenomena. [20][21][22][23] Various types of generalized derivatives were introduced ever, similar to Grunwald-Letnikov, Riesz, Riemann-Liouville, Caputo, and so forth. Most of them are described by methods for generalized integrals; hence, they obtain nonlocal properties from classic integrals.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized calculus is an astonishing and ground‐breaking subject for showing nonlinear systems. Lately, applications of generalized calculus are frequently appeared to unveil the behavior of multiple nonlinear phenomena 20‐23 . Various types of generalized derivatives were introduced ever, similar to Grunwald‐Letnikov, Riesz, Riemann‐Liouville, Caputo, and so forth.…”
Section: Introductionmentioning
confidence: 99%